Effect of Different Wheat Sprouting Conditions on the Characteristics of Whole-Wheat Flour - Navarro, José Luis (2024)
Research background. Controlled sprouting promotes physiological and biochemical changes in whole grains, improves their nutritional value and offers technological advantages for breadmaking as an alternative to traditional whole grains. The aim of this study is to find sprouting conditions for the grains of Klein Valor wheat variety (Triticum aestivum L.) that would increase the nutritional value without significantly affecting the gluten proteins, which are essential in wholegrain baked goods. Experimental approach. The chemical and nutritional composition, enzymatic activity and pasting properties of the suspensions of unsprouted and sprouted whole-wheat flour were evaluated. Results and conclusions. This bioprocess allowed us to obtain sprouted whole-wheat flour with different degrees of modification in its chemical composition. Sprouting at 25 °C resulted in an observable increase in enzymatic activity and metabolic processes, particularly α-amylases, which significantly affect the starch matrix and the associated pasting properties. Additionally, there was a smaller but still notable effect on the structure of the cell walls and the protein matrix due to the activation of endoxylanases and proteases. In contrast, sprouting at 15 and 20 °C for 24 h allowed for better process control as it resulted in nutritional improvements such as a higher content of free amino acid groups, free phenolic compounds and antioxidant capacity, as well as a lower content of phytates. In addition, it provided techno-functional advantages due to the moderate activation of α-amylase and xylanase. A moderate decrease in peak viscosity of sprouted whole-wheat flour suspensions was observed compared to the control flour, while protein degradation was not significantly prolonged. Novelty and scientific contribution. Sprouted whole-wheat flour obtained under milder sprouting conditions with moderate enzymatic activity could be a promising and interesting ingredient for wholegrain baked goods with improved nutritional values and techno-functional properties. This approach could avoid the use of conventional flour improvers and thus have a positive impact on consumer acceptance and enable the labelling of the product with a clean label.